Specificity of the STAT4 genetic association for severe disease manifestations of systemic lupus erythematosus. - Kimberly E Taylor; Elaine F Remmers; Annette T Lee; Ward A Ortmann; Robert M Plenge; Chao Tian; Sharon A Chung; Joanne Nititham; Geoffrey Hom; Amy H Kao; F Yesim Demirci; M Ilyas Kamboh; et al. (PLoS Genetics)
Systemic lupus erythematosus (SLE) is a genetically complex disease with heterogeneous clinical manifestations. A polymorphism in the STAT4 gene has recently been established as a risk factor for SLE, but the relationship with specific SLE subphenotypes has not been studied. We studied 137 SNPs in the STAT4 region genotyped in 4 independent SLE case series (total n = 1398) and 2560 healthy controls, along with clinical data for the cases. Using conditional testing, we confirmed the most significant STAT4 haplotype for SLE risk. We then studied a SNP marking this haplotype for association with specific SLE subphenotypes, including autoantibody production, nephritis, arthritis, mucocutaneous manifestations, and age at diagnosis. To prevent possible type-I errors from population stratification, we reanalyzed the data using a subset of subjects determined to be most homogeneous based on principal components analysis of genome-wide data. We confirmed that four SNPs in very high LD (r(2) = 0.94 to 0.99) were most strongly associated with SLE, and there was no compelling evidence for additional SLE risk loci in the STAT4 region. SNP rs7574865 marking this haplotype had a minor allele frequency (MAF) = 31.1% in SLE cases compared with 22.5% in controls (OR = 1.56, p = 10(-16)). This SNP was more strongly associated with SLE characterized by double-stranded DNA autoantibodies (MAF = 35.1%, OR = 1.86, p<10(-19)), nephritis (MAF = 34.3%, OR = 1.80, p<10(-11)), and age at diagnosis<30 years (MAF = 33.8%, OR = 1.77, p<10(-13)). An association with severe nephritis was even more striking (MAF = 39.2%, OR = 2.35, p<10(-4) in the homogeneous subset of subjects). In contrast, STAT4 was less strongly associated with oral ulcers, a manifestation associated with milder disease. We conclude that this common polymorphism of STAT4 contributes to the phenotypic heterogeneity of SLE, predisposing specifically to more severe disease.